PLANEACIÓN ESTRATÉGICA DE LA COOPERATIVA DE AHORRO Y CRÉDITO 27 DE ABRIL DE LA PARROQUIA DE CHUQUIRIBAMBA, EN LA PROVINCIA DE LOJA, SOCIA DE LA RED DE ENTIDADES FINANCIERAS EQUITATIVAS (REFSE) EN LA REGION SIETE - JARAMILLO GUARNIZO, CRISTINA DE LOS ÀNGELES (2012)
The finances are part of the economy of a sector, but contrary to other services from their origin have been conceived as a tool that allows the economic development. Our thesis has as specific objective a strategic plan that allows to the Savings and loan cooperative to settle down “April 27” to fulfill the objectives to short and medium term to improve the quality and excellence from its services to the community and it is subject in the following outline: The mask that contains as denominated title “Strategic Gliding of the Savings and loan cooperative “April 27” of the Parish of Chuquiribamba, in the County of Loja, Partner of the net of equal Financial entities (REFSE) in the region seven”, which will be seen the names of who it is realized, besides containing a certification that authorizes their realization, besides possessing a responsibility, gratefulness and dedication on the part of the Tesistas, then has the summary where is expressed the content of the investigation shortly, later on we have the introduction that contains importance, contribution and it structures of the work, next the theoretical mark defined by concepts among them finds Financial System, Concept of cooperative, agency Concept and branch, saving Concept and credit, Foundations of the Strategic Gliding, Analysis Foda, Financial Analysis, History of the COAC, Partners Founders, Legal Base, Corporate Philosophy, Gobernabilidad, etc., Analysis of the Strategic Plan, followed by a methodology used in this investigation through different methods like the deductive and inductive, also of procedures like the direct observation, analysis and synthesis, other techniques that she allowed to carry out a brief diagnosis of the current situation of the cooperative through of the interview and bibliographical summary being like necessary instrument the shop, also bill with having been through of the vertical and horizontal analysis of the balance sheet and of results and interpretation of financial indicators of the COAC APRIL 27 where its solid and stable financial setup is known, it is necessary to point out that the FODA is due important part that was remarked internal and external factors helping this way to the solution of the different problems raised in the entity being necessary to carry out an operative plan or of action to execute the different activities outlined through of the realized proposal to strengthen its image and prestige, the discussion of the work is the important part of this project where all that is summarized proposed waiting that they are taken into account for the achievement of the objectives, when arriving to the summations and recommendations she makes it to him so that she takes to consideration certain aspects for the change and progress of the entity, the bibliographical sources that took into account to base this work, however all the delivered documents on the part of the cooperative are part of the annexes, and to conclude the index that gives form to the content outline, the same one that one will be able to know with accuracy all it with respect to the realized work.